Metode Dakwah Dalam Memakmurkan Masjid Mamba'ul Huda Kecamatan Jatisrono Kabupaten Wonogiri - Ernawati Ernawati (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2022)
The prosperity of the mosque is essential for Muslims, as the mosque serves as a location for a variety of worship activities. The purpose of this study was to analyze the preaching method to prosper the Mamba’ul Huda Mosque. In this study uses qualitative descriptive method with data collection through interviews, observation and documentation. The results of this study are preaching method in the form of reciting caberawit, disciplinary preaching, routine recitation of mothers, tahfizul qur'an, and preaching of cleanliness. One of the benefits of the prosperity of the mosque is that people are protected from various disasters, including diseases, mass riots and others.